2021
DOI: 10.1093/nar/gkab203
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of influenza nucleoprotein complexed with nucleic acid provide insights into the mechanism of RNA interaction

Abstract: The nucleoprotein (NP) of influenza virus is the core component of the ribonucleoprotein (RNP) and performs multiple structural and functional roles. Structures of the influenza A, B and D NP molecules have been solved previously, but structural information on how NP interacts with RNA remains elusive. Here we present the crystal structure of an obligate monomer of H5N1 NP in complex with RNA nucleotides to 2.3 Å, and a C-terminal truncation of this mutant, also in complex with RNA nucleotides, to 3 Å. In both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…In fact, the NSV genomes are never free of NP in nature. For many NSVs, direct evidence on the RNA-binding mechanism has been proven by co-crystallization of the RNA–NP complexes [ 47 , 63 , 65 , 75 , 76 , 77 ]. Essential for the protective function of NP is its capacity to tightly bind the RNA and oligomerize and shape a helical RNC.…”
Section: Structure and Function Of Npmentioning
confidence: 99%
“…In fact, the NSV genomes are never free of NP in nature. For many NSVs, direct evidence on the RNA-binding mechanism has been proven by co-crystallization of the RNA–NP complexes [ 47 , 63 , 65 , 75 , 76 , 77 ]. Essential for the protective function of NP is its capacity to tightly bind the RNA and oligomerize and shape a helical RNC.…”
Section: Structure and Function Of Npmentioning
confidence: 99%
“…Furthermore, we mapped this change to a predicted structure of the NP protein and we were able to demonstrate that it is present on an exposed surface ( Figure 3D ). It has been demonstrated that the NP 360-373 loop is critical in RNA binding ( 21 ). Importantly, none of the viral isolates had incorporated multiple basic amino acids in the cleavage site of the HA protein ( Figure 3A ), which is recognized as the major determinant of AI virus pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the changes we have observed in the NP may have led to increased pathology through changes in peptide/MHCI-TCR interactions. In addition to the impact on T cell subtypes, the mutation in the NP protein it has been demonstrated that the NP 360-373 loop is critical in RNA binding ( 21 ). This role in the stabilization of RNA is an essential role of NP in replication of the virus and may lead to increased proliferation potential.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Because both NP mutants contain alanine substitutions in residues 213, 214, and 216, which are located close to the RNA-binding groove formed by R74, R75, R174, R175, and R221 (NP-G1 region) ( 31 33 ), such mutations potentially alter the RNA-binding property of NP and subsequent RNP formation ( 34 ). However, NoLS-NP NoLSmut , which contains alanine substitutions in the intrinsic NoLS but has an ectopic NoLS at the amino terminus, had the ability to form functional double-helical RNPs (see Fig.…”
Section: Discussionmentioning
confidence: 99%